Manajemen Bencana Banjir Dalam Meningkatkan Ketahanan Wilayah Oleh BPBD Kota Semarang - Marta, Dwi Jati; Fersari, Tika Pustika (Jurnal Riptek, 2025)
This study aimed to analyze the factors that hindered and supported flood disaster management conducted by the Badan Penanggulangan Bencana Daerah (BPBD) Kota Semarang. The analysis method used in this study was descriptive qualitative analysis with a case study approach. Data were obtained through interviews with relevant parties, field observations, and documentation. The results showed that the main hindering factors were the low awareness of the community and stakeholders, limited human resources, logistics, funding, and the lack of accurate data. On the other hand, significant supporting factors included external support from community organizations, volunteers, and good coordination between BPBD and relevant regional agencies (OPD). The presence of Kelurahan Siaga Bencana (KSB) and Kelurahan Tangguh Bencana (KTB) strengthened BPBD’s capacity to manage flood disasters. Furthermore, the involvement of local actors and the integration of community-based disaster risk reduction efforts played a critical role in enhancing territorial resilience. This study suggested that BPBD Kota Semarang should strengthen coordination, enhance public education and awareness, and improve the data system to improve the effectiveness of disaster management and promote sustainable territorial resilience in the future.Kata Kunci: Disaster Management, Disaster Prepared, Disaster Risk Reduction, Floods, Resilient Villages